The role of sensory ecology and cognition in social decisions: Costs of acquiring information matter. (9th February 2020) - Schneeberger, Karin; Taborsky, Michael
Abstract: We generally assume that animals should maximize information acquisition about their environment to make prudent decisions. But this is a naïve assumption, as gaining information typically involves costs. This is especially so in the social context, where interests between interacting partners usually diverge. The arms race involved in mutual assessment is characterized by the attempt to obtain revealing information from a partner while providing only as much information by oneself as is conducive to one's own intentions. If obtaining information occasions costs in terms of time, energy and risk, animals should be selected to base their decisions on a cost–benefit ratio that takes account of the trade‐off between the risk of making wrong choices and the costs involved in information acquisition, processing and use. In addition, there may be physiological and/or environmental constraints limiting the ability to obtaining, processing and utilizing reliable information. Here, we discuss recent empirical evidence for the proposition that social decisions are to an important extent based on the costs that result from acquiring, processing, evaluating and storing information. Using examples from different taxa and ecological contexts, we aim at drawing attention to the often neglected costs of information recipience, with emphasis on the potential role of sensory ecology and cognition in social decisions.